Topographic Pattern of Keratoconus patient at First Presentation in Tertiary Eye Hospital of Bangladesh - Mallick, Abeer; Romance, Naoroze Ferdous; Akter, Yasmin; Islam, Md Atikul; Dey, Hymonti; Quader, Md Abdul (Journal of National Institute of Ophthalmology, 2022)
Objective: To evaluate the topographic pattern of keratoconus patient at first presentation in a tertiary eye hospital of Bangladesh. Methods: This was a cross sectional study conducted over 200 eyes of 100 keratoconus patients attending at National Institute of Ophthalmology & Hospital, Dhaka, for a period of 6 months. Selected patients underwent detail history, ocular and systemic examination as well as related investigations which includes corneal topography, keratometry and auto refractometry. Results: Mean age of the patients was 21.24 ± 6.25(SD) years and among the patients male predominance was observed, male to female ratio was 2.1:1. The mean unaided visual acuity of better eye was 0.86 ± 0.38(SD) Log MAR and mean unaided visual acuity of worse eye was 1.16 ± 0.44 Log MAR. Among 200 eyes there were 36 mild (18.0%), 100 moderate (50.0%) and 64 severe (32.0%) keratoconus eyes. Majority of the eyes (81.0%) showed three common topographic pattern, these are asymmetric bowtie with skewed axis (32.0%), asymmetric bowtie with inferior steepening (30.0%) and inferior steepening (19.0%). In mild keratoconus patients topography showed largely one pattern, inferior steepening (30.6% of mild keratoconus). In case of moderate keratoconus patients topography shows mainly three patterns, asymmetrical bowtie with skewed axis (19.0%), asymmetric bowtie with inferior steepening (16.5%) and inferior steepening (10.5%). In severe keratoconus patients topography shows mainly three patterns, asymmetrical bowtie with inferior steepening (10.5%), asymmetric bowtie with skewed axis (9.5%) and irregular pattern (8.5%). There was no round, superior steepening, symmetric bowtie or asymmetric bowtie with superior steepening pattern in severe keratoconus. Conclusion: The pattern of topography varies among the different stages of keratoconus patients. From the topography pattern we can diagnose the keratoconus early and also get the information of severity of the disease and treat accordingly. J. Natl. Inst. Ophthalmol. 2022; 5(2):31-36